Permutations of a Self : Poems - Nguyen, Thomas (Book collections on Project MUSE., 2020)
"Permutations of a Self grapples with issues of belonging and connection, all from the perspective of someone who does a lot more observing and ruminating than living in the present. Most of the poems draw from Nguyen's imperfect memory of himself and others as it changes throughout time. In many ways, the poet feels like an outsider in his own family because he has gradually forgotten how to speak Vietnamese, his native language that he once knew so well. The poems in this manuscript are as much about coming to terms with that as they are about trying to reconcile what it means to be a part of his family. Interspersed throughout are threads connecting the poet to each one of his family members. They are the moments he turns back to again and again when he is lonely, confused, or unsure about where he comes from and where he is going"--